Prosopos in Student Communication with Generative AI: A Phenomenological Study of Persona Formation and AI Literacy in Digital Higher Education - Fery Harianto; Rajab Ritonga; Pitoyo Pitoyo (Journal of Social Research, 2026)
The emergence of Generative Artificial Intelligence (AI) has significantly transformed digital communication in higher education, enabling natural language interactions that resemble interpersonal dialogue. This study investigates how students construct communicative relationships with AI and develop AI literacy in academic contexts. The research aims to explore students' experiences in assigning personas to AI, engaging in "as-if human" communication, and reflecting ethically on AI usage. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed, involving 25 students from the D-III Public Relations Program at AKMRTV Jakarta. Data were collected through in-depth interviews, digital observations, and analysis of 218 AI conversational documents. The findings reveal that students perceive AI as an academic thinking partner, discussion companion, and virtual mentor, fostering relational attachment and supporting idea development. Students actively assign personas to AI platforms, applying interpersonal communication norms and critical verification during interactions. Based on these insights, the Prosopopoeic AI Literacy (PAIL) model was developed, consisting of five dimensions: Persona Awareness, Relational Awareness, Critical Verification, Academic Agency, and Ethical Reflection. The study concludes that AI literacy encompasses both technical skills and reflective, ethical, and relational competencies, positioning AI as a quasi-social actor in higher education. These findings provide practical implications for AI integration into curricula, promoting responsible, ethical, and effective human-AI communication in academic environments.